Saberes mobilizados por professores quando o foco são as provas matemáticas: um estudo de caso - Leandro, Ednaldo José (2012)
Through a study conducted with five teachers of municipal schools of São Paulo, a survey was carried out which knowledge is mobilized by them, when the focus is on mathematical proofs in elementary school. The text portrays the motivations and obstacles encountered by teachers in developing classroom issues related to mathematical proofs, as well as its functions and typologies aimed. For the development of the research, we used the case study and theoretical reference, the following works: Tardif, on teacher knowledge, the types and functions of mathematical proofs of Balacheff and de Villiers, respectively. The following instruments were used to collect data: direct observation, field notes, interviews, and survey activities. The results point to the mobilization of some knowledge, namely: Curriculum, Experiential and Disciplinary. It was also found that teachers perceive the development of mathematical proofs as a process, considering them an important element to make students develop the habit of presenting justifications for their elaborations. Knowing to do an exam was pointed as a skill to be acquired relevant not only for mathematics, but also for the life of apprentice after school, besides being an opportunity to realize the structure, beauty and connections of mathematical ideas. The productions of mathematical proofs, prepared by students, are identified by teachers as being predominantly pragmatic, at this level of education, and used to explain the function and hence to convince